Compassion fatigue and secondary traumatic stress in teachers: How they contribute to burnout and how they are related to trauma-awareness - Oberg, Glenys; Carroll, Annemaree; Macmahon, Stephanie (Frontiers in Education, 2023)
Teachers play an integral role in providing positive life experiences for their students and are especially crucial for students who are experiencing or have experienced a trauma in their lives. In Australia however, teachers are increasingly stating that they do not plan on remaining in the profession causing media and governments to warn of a teacher shortage. Several key factors for teacher attrition have been proposed, with burnout being described as a contributing factor). Studies which have focussed specifically on teachers’ experiences working with students with histories of trauma have suggested links between lack of trauma-aware training and increased levels of compassion fatigue (CF), secondary traumatic stress (STS), and burnout. This paper draws on established research into CF, STS and burnout as well as trauma awareness of teachers using a narrative topical approach to explore the challenges faced by teachers and students in a post-covid landscape. The results of this review suggest a need for additional research into the impact on teachers of working with an increasingly traumatised student body. The lack of trauma-specific training reported by pre-service and current teachers indicate a need for higher education institutions and schools to better prepare teachers to support traumatised students while safeguarding their own wellbeing.